SCD1 Sustains Homeostasis of Bulge Niche via Maintaining Hemidesmosomes in Basal Keratinocytes - Yueqing Xue; Liangyu Lin; Qing Li; Keli Liu; Mingyuan Hu; Jiayin Ye; Jianchang Cao; Jingjie Zhai; Fanjun Zheng; Yu Wang; Tao Zhang; Liming Du; et al. (Advanced Science, 2023)
Abstract Niche for stem cells profoundly influences their maintenance and fate during tissue homeostasis and pathological disorders; however, the underlying mechanisms and tissue‐specific features remain poorly understood. Here, it is reported that fatty acid desaturation catabolized by stearoyl‐coenzyme A desaturase 1 (SCD1) regulates hair follicle stem cells (HFSCs) and hair growth by maintaining the bulge, niche for HFSCs. Scd1 deletion in mice results in abnormal hair growth, an effect exerted directly on keratin K14+ keratinocytes rather than on HFSCs. Mechanistically, Scd1 deficiency impairs the level of integrin α6β4 complex and thus the assembly of hemidesmosomes (HDs). The disruption of HDs allows the aberrant activation of focal adhesion kinase and PI3K in K14+ keratinocytes and subsequently their differentiation and proliferation. The overgrowth of basal keratinocytes results in downward extension of the outer root sheath and interruption of bulge formation. Then, inhibition of PI3K signaling in Scd1−/− mice normalizes the bulge, HFSCs, and hair growth. Additionally, supplementation of oleic acid to Scd1−/− mice reestablishes HDs and the homeostasis of bulge niche, and restores hair growth. Thus, SCD1 is critical in regulating hair growth through stabilizing HDs in basal keratinocytes and thus sustaining bulge for HFSC residence and periodic activity.